29th November 1st Sunday of Advent - Janklow, Aaron (2015)
The article presents a sermon by Aaron Janklow, assistant minister at St. Giles' Cathedral in Edinburgh, Scotland for the 1st Sunday of Advent on November 29, 2015. Topics covered include the 21st chapter of Luke's Gospel, Advent as a time of waiting and anticipation, and the parable of a fig tree provided by Jesus Christ.
Keywords: Advent; ADVENT sermons; Bible; Bible. Luke; Bible -- Parables; Jesus Christ; Jesus Christ -- Parables; Parables